The Physical and Social Values of Homegarden Vegetations to Reduction of Suspended Particulate Matter-SPM- Value in Gunung Putri Village, Gunung Putri Regenct, Bogor - Merzyta Septiyani; Rachmad Hermawan; Arzyana Sunkar (Media Konservasi, 2009)
This research has the objective to determine the physical and social values of homegarden vegetation that influenced the reduction of SPM value on air, and the factors related to community attitudes and functions and existence of homegarden. Research results showed that SPM on air experienced a decline with increasing vegetation shade. Height of tree and LAI were negatively correlated with SPM values, meaning in an increase of LAI values and tree height would reduce the value of SPM. Tree height significantly effect (P-valeu=0.021<α) on reducing SPM by (y=920.4-59.66x) and LAI also has significantly effect (P-value=0.092< α) in reducing SPM by (y=2762-944.8x). The majority of respondents (76.74%) had positive attitudes, meaning that they understand and directly felt the benefit of homegarden, while the rest had average value of attitudes. Attitudes directly influences by tha age, duration of living in the area and occupation. Keywords: Suspended Particulate Matter (SPM), vegetation, homegarden, attitude